EZH2 contributes to 5-FU resistance in gastric cancer by epigenetically suppressing FBXO32 expression - Wang, Chenyu (Onco Targets Ther, 2018)
BACKGROUND: Increasing evidence suggests the involvement of enhancer of zeste homologue 2 (EZH2) in chemoresistance of cancer treatment. Nevertheless, its function and molecular mechanisms in gastric cancer (GC) chemoresistance are still not well elucidated. MATERIALS AND METHODS: In the present study, we investigated the functional role of EZH2 in 5-fluorouracil (5-FU) resistance of GC cells and discovered the underlying molecular mechanism. RESULTS: Results revealed that EZH2 was upregulated in 5-FU-resistant GC tissues and cell lines. High ZEH2 expression was correlated with poor prognosis of GC patients. EZH2 knockdown enhanced 5-FU sensitivity of AGS/5-FU and SGC-7901/5-FU cells. Moreover, EZH2 could epigenetically suppress FBXO32 expression. FBXO32 overexpression could mimic the functional role of downregulated EZH2 in 5-FU resistance. FBXO32 knockdown counteracted the inductive effect of EZH2 inhibition on 5-FU sensitivity of AGS/5-FU and SGC-7901/5-FU cells. Furthermore, EZH2 knockdown facilitated 5-FU sensitivity of 5-FU-resistant GC cells in vivo. CONCLUSION: In summary, EZH2 depletion overcame 5-FU resistance in GC by epigenetically silencing FBXO32, providing a novel therapeutic target for GC chemoresistance.